A Literature Review of Performance Metrics of Automated Driving Systems for On-Road Vehicles - Sharath, Mysore Narasimhamurthy; Mehran, Babak (Frontiers in Future Transportation, 2021)
The paper presents a review of recent literature on the performance metrics of Automated Driving Systems (ADS). More specifically, performance indicators of environment perception and motion planning modules are reviewed as they are the most complicated ADS modules. The need for incorporation of the level of threat an obstacle poses in the performance metrics is described. A methodology to quantify the level of threat of an obstacle is presented in this regard. The approach involves simultaneously considering multiple stimulus parameters (that elicit responses from drivers), thereby not ignoring multivariate interactions. Human-likeness of ADS is a desirable characteristic as ADS share road infrastructure with humans. The described method can be used to develop human-like perception and motion planning modules of ADS. In this regard, performance metrics capable of quantifying human-likeness of ADS are also presented. A comparison of different performance metrics is then summarized. ADS operators have an obligation to report any incident (crash/disengagement) to safety regulating authorities. However, pre-crash events/states are not being reported. The need for the collection of the pre-crash scenario is described. A desirable modification to the data reporting/collecting is suggested as a framework. The framework describes the pre-crash sequences to be reported along with the possible ways of utilizing such a valuable dataset (by the safety regulating authorities) to comprehensively assess (and consequently improve) the safety of ADS. The framework proposes to collect and maintain a repository of pre-crash sequences. Such a repository can be used to (i) comprehensively learn and model the pre-crash scenarios, (ii) learn the characteristics of pre-crash scenarios and eventually anticipate them, (iii) assess the appropriateness of the different performance metrics in pre-crash scenarios, (iv) synthesize a diverse dataset of pre-crash scenarios, (v) to identify the ideal configuration of sensors and algorithms to enhance safety, and (vi) monitor the performance of perception and motion planning modules.